2011
DOI: 10.1007/s11252-011-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Trees for urban environments in northern parts of Central Europe – a dendroecological study in north-east Romania and Republic of Moldavia

Abstract: A limited number of species and genera currently dominate the tree stock in streets and urban sites. There has been considerable and persistent argumentation for the necessity of using a more varied and stress-tolerant selection of tree species. This paper reports results from a dendroecological study of six steppe forest reserves in north-east Romania and in the adjacent part of the Republic of Moldavia, where water stress regimes during the growing season and winter temperatures are comparable to those of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…and Fagus sylvatica (Kausch‐Blecken von Schmeling 1994b; Schrötter ). Growth also varies across the range of S. torminalis from 35 to 60 cm year −1 in Germany (Kausch‐Blecken von Schmeling , 1994b; Schüte ) to a mean of 21 cm year −1 in north‐east Romania and Moldavia (Sjöman, Nielsen & Oprea ). However, age of the tree appears to be a more important determinant of growth, with annual growth rates of between 20 and 100 cm year −1 in the first 10–18 years, falling to 15–25 cm year −1 at 50 years old and 5 cm year −1 at 70 years old (Röhrig ; Crave ; Bamberger ; Schüte ; Kahle ).…”
Section: Response To Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…and Fagus sylvatica (Kausch‐Blecken von Schmeling 1994b; Schrötter ). Growth also varies across the range of S. torminalis from 35 to 60 cm year −1 in Germany (Kausch‐Blecken von Schmeling , 1994b; Schüte ) to a mean of 21 cm year −1 in north‐east Romania and Moldavia (Sjöman, Nielsen & Oprea ). However, age of the tree appears to be a more important determinant of growth, with annual growth rates of between 20 and 100 cm year −1 in the first 10–18 years, falling to 15–25 cm year −1 at 50 years old and 5 cm year −1 at 70 years old (Röhrig ; Crave ; Bamberger ; Schüte ; Kahle ).…”
Section: Response To Environmentmentioning
confidence: 99%
“…Stem diameter growth varies with competition, and annual ring width may be as low as 1–2 mm in woodland while individuals in the open can have ring widths of 2·5–4·0 mm (Sevrin & Keller ; Hochbichler ; Kahle ; Sjöman, Nielsen & Oprea ) although Rasmussen () recorded mean tree ring widths of up to 16·1 mm in central Germany. Age is also a large factor in diameter growth.…”
Section: Response To Environmentmentioning
confidence: 99%
“…Previous studies listed different explanatory factors to urban tree decline. Among them, pollution, pruning, soil conditions or individual tree characteristics could be involved in urban tree decline (Roberts 1977;Kjelgren and Clark 1992;Lin et al 2006;Nielsen et al 2007;Sjöman et al 2012;Moser et al 2016b). However, several studies have shown that drought could be the main inciting factor impacting urban trees health and survival (Roberts 1977;Apple and Manion 1986;Clark and Kjelgren 1989;Whitlow et al 1992;McCarthy and Pataki 2010;Gillner et al 2013;Gillner et al 2014;Vico et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in age-specific responses of trees to climate are often addressed in literature (Carrer and Urbinati 2004;Linares et al 2013) but, to our knowledge, no such study was conducted on street trees. In this context, dendrochronology is a useful tool to study the relationship between tree growth and climatic factors such as temperature and precipitation in urban environment (Fritts 1976;Sjöman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Eastern Romania has been identified as a future source area of plants for inner-city environments of Scandinavia, as its native plants are exposed to similar climate and stress regimes as those associated with urban paved sites (Sjöman, Richnau, 2009;Sjöman et al, 2012). Due to the higher summer temperatures and lower rainfall compared with Western Europe, large areas of steppe communities have developed in eastern Romania (Breckle, 2002).…”
Section: Introductionmentioning
confidence: 99%